How to Name Invisible Principles? The Challenge of Naming What the Eyes Cannot See - Peixoto, Miriam Campolina Diniz (Revista Archai, 2024)
What were the guidelines that the ancient atomists followed when coining new terms to name their principles? To what extent the difficulty of apprehension and understanding of the nature of their principles would justify the use of more than one term for naming the same thing? Some modern scholars tend to reduce the “indivisible” to a mere formal principle, while other scholars insist in considering the “indivisible” as a material principle. Can anyone find in the ancient texts sufficient elements to evaluate these claims without losing sight of the particular horizon of inquiry and conceptual universe of Presocratic philosophy? I intend to map the problem of the names assigned to the principles in the atomists’ thought in order to formulate a few hypotheses concerning some issues that seem to underlie the transmission and the reception of their thought in antiquity.